Reduction of macular oedema by acetazolamide in patients with chronic iridocyclitis: a randomised prospective crossover study. Issue 1 (January 1994) - Farber, M D; Lam, S; Tessler, H H; Jennings, T J; Cross, A; Rusin, M M
Abstract : Thirty patients with cystoid macular oedema secondary to chronic iridocyclitis were enrolled in a two period, prospective, randomised, double masked, crossover study that compared sustained release acetazolamide (500 mg twice a day) with a placebo to measure the effects on the reduction of cystoid macular oedema and improvement of visual acuity. All patients were treated for 1 month with either acetazolamide or placebo, received no treatment for 1 month, and were then treated for 1 month with the other medication. Statistically significant improvement in visual acuity was seen at 14 and 28 days in the treated patients. No improvement was seen when patients received placebo. Improved visual acuity was not associated with race or sex. However, younger patients (under age 55 years) were more likely to benefit from treatment. Results of vitreous fluorophotometry, obtained at baseline and 4 weeks, demonstrated an improvement in posterior vitreous penetration ratios and mid vitreous penetration ratios after treatment with acetazolamide but not with placebo.